The Estimate of Heterosis Effects of Sheep Body Weights in Different Ages - Abdullah Hameed Salim (Journal of Global Pharma Technology, 2018)
The current study was carried out at the Radwaniyah station / Ministry of Agriculture, which included analysis of data of local awassi sheep, Assaf and crossing Assaf (local Awassi ×Assaf). Records included weights at birth and weaning and in ages of 6, 9 and 12 months for the three genetic groups above. We aimed to study the effect of the genetic group on the lamb’s weights at different ages and the effects of the hybrid vigor resulting from the crossing of local awassi sheep with Assaf sheep to the traits of the weights in ages from birth to one year old. The results showed that the genetic group had a significant effect (p˂0.01) in all the studied traits while the effect of hybrid vigor was not significant for all studied traits, but it was similar to some previous studies, with 10.36, 12.20, 5.80, 6.49 and 4.92 % for weights at birth, weaning, 6 months, 9 month and 12 month respectively.